Inter- Not Intraindividual Differences in sTWEAK Levels Predict Functional Deterioration and Mortality in Patients with Dilated Cardiomyopathy - Kai-Uwe Jarr; Manfred Nelles; Hugo A. Katus; Emmanuel Chorianopoulos (Mediators of Inflammation)
Background. TNF-like weak inducer of apoptosis (TWEAK) has been reported to predict mortality in patients with dilated cardiomyopathy. However, whether it can be used as a biomarker for disease monitoring or rather represents a risk factor for disease progression remains unclear. Aim of the Study. To evaluate the potential of sTWEAK as a biomarker in patients with dilated cardiomyopathy. Results. We conducted a serial study of sTWEAK levels in 78 patients with dilated cardiomyopathy. Soluble TWEAK levels predicted not only a combined mortality/heart transplantation endpoint after 4 years (P=0.0001), but also the risk for clinical deterioration (P=0.0001). Compared to NT-proBNP, sTWEAK remained relatively stable in individual patients on follow-up indicating that inter- rather than intraindividual differences in sTWEAK levels predicted outcome. Finally, neither did the scavenger receptor sCD163 correlate with sTWEAK levels nor did its determination add additional information on outcome in patients with dilated cardiomyopathy. Conclusion. Soluble TWEAK levels in patients with dilated cardiomyopathy may not be of value for disease monitoring but may represent a risk factor for disease progression and death. Further research will be necessary to elucidate the exact role of sTWEAK as a potential modulator of immune response in the setting of dilated cardiomyopathy.